Environmental Variables and Spatiotemporal Occurrence of Johnius belangerii (Cuvier, 1830) Belanger’s Croaker: An Analysis Using Boosted Regression Trees - Karankumar K. Ramteke; L Shenoy; B. B. Nayak; G. Deshmukhe; A. B. Inamdar; V. V. Singh (Journal of Indian Fisheries Association, 2020)
The objective of this research was to assess the influence of environmental factors aﬀecting spatio-temporal distribution of Johnius belangerii (Cuvier, 1830). In order to determine the impact of environmental variables on spatio-temporal distribution, fortnightly independent fishery resource surveys were conducted in Mumbai waters from September 2017 to May 2019. An integration of a high percentage of bottom temperature (BT), bottom chlorophyll-a (BTChla), sea surface height (SSH) and surface chlorophyll-a (chl-a) has been found to favour the spatio-temporal distribution of J. belangerii. The study supports the fact that a systematic approach can provide a better understanding of a spatio-temporal distribution pattern along with ecological data in the statistical models. The outcome of this analysis will be useful for a better understanding of the dynamics of fish with respect to spatial distribution in relation to evolving habitat conditions, which will be useful for the sustainable management of the resource.